PERUBAHAN PENDAPATAN PEDAGANG UMKM (USAHA MIKRO KECIL MENENGAH) SELAMA MASA PEMBANGUNAN IPAL (INSTALASI PENGOLAHAN LIMBAH) DAN PANDEMI COVID-19 DI KECAMATAN SUKAJADI KOTA PEKANBARU PROVINSI RIAU - Noviani Syabrina; Deded Chandra (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to determine the changes in income earned by Micro, Small and Medium Enterprises (MSME) traders before and during the construction of the Waste Water Treatment Plant (WWTP) and the Covid-19 pandemic in Sukajadi District, Pekanbaru City. The type of research used is descriptive with a quantitative approach, analyzed before and during the construction of WWTP (Wastewater Treatment Plant) and the Covid-19 pandemic on the income of MSME traders in Sukajadi District using secondary data as a data source as many as 51 samples. This analysis uses a non-parametric approach with the Wilcoxon signed rank test because the results of the normality test of the data are not normally distributed because the significance value is below 0.05. The results of the study showed that there was a significant decrease in MSME (Micro, Small and Medium Enterprises) actors in Sukajadi District on their income during the construction of WWTPs (Wastewater Treatment Installations) and the Covid-19 pandemic.